The Effect Of Job Satisfaction On Employees' Organizational Commitment At Gattareng Village Office, Soppeng Regency - Andi Rahma Nur Alam; Asni Asni; Febbi Feria (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study aims to examine the effect of job satisfaction on organizational commitment of employees at the Gattareng Village Office, Soppeng Regency. This study uses a quantitative approach with a simple linear regression analysis method to determine how much influence job satisfaction has on organizational commitment. The sample used in this study was 14 employees of the Gattareng Village Office. Data were collected through a questionnaire containing questions related to working conditions, awards, compensation, and career development. The results of the study indicate that job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction, which consists of various factors such as the physical condition of the workplace, recognition and awards, compensation and benefits, and career development opportunities, directly affects employee commitment to the organization. The higher the employee's job satisfaction, the higher their commitment to the Gattareng Village Office. This study provides recommendations for the Gattareng Village Office to improve aspects that affect employee job satisfaction, such as improving compensation and benefits, providing fairer awards, and providing more opportunities for career development. In this way, it is expected to increase employee organizational commitment, which in turn will improve the quality of public services at the Gattareng Village Office